2016
DOI: 10.1089/chi.2015.0083
|View full text |Cite
|
Sign up to set email alerts
|

Passive Smoke Exposure and Its Effects on Cognition, Sleep, and Health Outcomes in Overweight and Obese Children

Abstract: Background: Passive smoke exposure (PSE) may be a risk factor for childhood overweight and obesity and is associated with worse neurocognitive development, cognition, and sleep in children. The purpose of the study is to examine the effects of PSE on adiposity, cognition, and sleep in overweight and obese children using an objective measure of PSE.Methods: Overweight or obese children (n = 222) aged 7-11 (9.4 -1.1 years; 58% black; 58% female; 85% obese) were recruited from schools near Augusta, Georgia, over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…One study was a non-randomised trial (Halberstadt 2017);Seven studies did not report the disaggregated data for children with obesity or overweight (Donnelly 2009; Donnelly 2013; Gentile 2009; Hillman 2014; Murray 2008; Puder 2011; Reed 2010);Two studies employed lifestyle interventions without the intention to prevent or reduce obesity (Crova 2014; Pesce 2016b);Eight studies used non-eligible tools to assess school or cognitive outcomes (e.g. self-reported or parent-reported questionnaires) (Gee 2014; Goldfield 2012; Muzaffar 2014; Naar-King 2016; Pentz 2011; Salmoirago-Blotcher 2015; Smith 2015; Wong 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study was a non-randomised trial (Halberstadt 2017);Seven studies did not report the disaggregated data for children with obesity or overweight (Donnelly 2009; Donnelly 2013; Gentile 2009; Hillman 2014; Murray 2008; Puder 2011; Reed 2010);Two studies employed lifestyle interventions without the intention to prevent or reduce obesity (Crova 2014; Pesce 2016b);Eight studies used non-eligible tools to assess school or cognitive outcomes (e.g. self-reported or parent-reported questionnaires) (Gee 2014; Goldfield 2012; Muzaffar 2014; Naar-King 2016; Pentz 2011; Salmoirago-Blotcher 2015; Smith 2015; Wong 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies employed lifestyle interventions without the intention to prevent or reduce obesity (Crova 2014; Pesce 2016b);…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in a Danish population determined that maternal prenatal smoking or use of nicotine replacement therapy was more strongly associated to an increased risk of ADHD in children than paternal tobacco use [29*]. A recent study in overweight and obese children found an association between plasma cotinine levels and poorer cognitive scores [30**], suggesting that environmental tobacco smoke exposure during childhood can impact brain development.…”
Section: Adverse Health Outcomesmentioning
confidence: 99%